Nonexistence of subnormal solutions for a class of higher order complex differential equations - Belaïdi, Benharrat; Zemirni, Mohamed Amine (Bulletin of the Transilvania University of Brasov. Mathematics, Informatics, Physics. Series III, 2015)
In this article, we investigate the existence of subnormal solutions for a class of higher order complex di erential equations. We generalize the result of N. Li and L. Z. Yang [14], L. P. Xiao [17] and also result of Z. X. Chen and K. H. Shon [4].
Keywords: Differential equation; hyper order; e-type order; ubnormal solution